(untitled) (Research, Society and Development, 2020)
Seeds are essential components of the economy, they contain life and the possibility of spreading diseases, and sanity is important for obtaining healthy plants with high yields. This work aimed to evaluate the sanitary quality of rice seeds of the Bonança variety and the reduction of phytopathogens, using seed microbiolization with Bacillus macerans, B. polymyxa, B. pentothenticus, B. lentus, B. pumilus, B. stearothermophilus e Bacillus sp.. For the seed health test, the Blotter Test method was used. In order to evaluate the reduction of the incidence of phytopathogens in the seeds, the microbiolization procedure was performed for each isolate and later the seeds were sown in sterile soil. The experimental design used was completely randomized in the laboratory and greenhouse experiments. The incidence and reduction of phytopathogens in rice seeds and plants was evaluated at seven and fourteen days after sowing. The seeds were evaluated using a magnifying glass to identify colonies of fungi. As for plants, 100 plants were removed in each season and the usual asepsis was performed. The results of the in vitro test of Bonança rice seeds, microbiolized with Bacillus spp., Reduced the incidence of Curvularia oryzae and Aspergillus niger. In plants originated from microbiolized seeds with Bacillus spp. a reduction in the incidence of the pathogens Curvularia oryzae, Aspergillus niger and Scopulariopsis sp. The action of the isolates was differentiated as to the pathogen and the time after microbiolization of the seeds.